Comparing shocks and frictions in US and euro area business cycles: a Bayesian DSGE approach - Frank Smets; Raf Wouters (European Central Bank (ECB), 2004)
This paper estimates a DSGE model with many types of shocks and frictions for both the US and the euro area economy over a common sample period (1974-2002). The structural estimation methodology allows us to investigate whether differences in business cycle behaviour are due to differences in the type of shocks that affect the two economies, differences in the propagation mechanism of those shocks or differences in the way the central bank responds to those economic developments. Our main conclusion is that each of those characteristics is remarkably similar across both currency areas.
Keywords: E1; E3; 330; business cycle fluctuations; DSGE Models